Ferrocene adsorbed into the porous octakis(hydridodimethylsiloxy) silsesquioxane after thermolysis in tetrahydrofuran media: An applied surface for ascorbic acid determination - do Carmo, Devaney Ribeiro [UNESP]; Paim, Leonardo Lataro [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Octakis(hydridodimethylsiloxi)silsesquioxane (Q(8)M(8)(H)) was synthesized and Ferrocene was adsorbed in a polymeric net through electrostatic interactions, with anion forming after the cleavage of any siloxy groups (ESFc). The nanostructured materials (Q(8)M(8)(H) and EsFc) were characterized by Fourier transform infrared spectra (FT-IR), nuclear magnetic resonance (NMR), X-ray diffraction (XRD), Thermogravimetric analyses and Voltammetric technique The cyclic voltammograms of the graphite paste electrode modified with ESFc showed one redox couple with E-0' = 0.320 V (1.0 mol L-1 NaCl, v = 50 mV s(-1)), with a diffusion-controlled process and the redox process shows electrocatalytic activity for the oxidation of ascorbic acid. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures.; Chemical synthesis; Electrochemical measurements; Nuclear magnetic resonance (NMR); Surface properties